2018
DOI: 10.1021/acs.inorgchem.7b03116
|View full text |Cite
|
Sign up to set email alerts
|

A Large Family of Centrosymmetric and Chiral f-Element-Bearing Iodate Selenates Exhibiting Coordination Number and Dimensional Reductions

Abstract: The exploration of phase formation in the f-element-bearing iodate selenate system has resulted in 14 novel rare-earth-containing iodate selenates, Ln(IO 3 )(SeO 4 ) (Ln = La, Ce, Pr, Nd; LnISeO-1), Ln(IO 3 )(SeO 4 )(H 2 O) (Ln = Sm, Eu; LnISeO-2), and Ln(IO 3 )(SeO 4 )(H 2 O) 2 •H 2 O (Ln = Gd, Dy, Ho, Er, Tm, Yb, Lu, Y; LnISeO-3), as well as two new thorium iodate selenates, Th(OH)(IO 3 )(SeO 4 )(H 2 O) (ThISeO-1) and Th(IO 3 ) 2 (SeO 4 ) (ThISeO-2). LnISeO-3 and ThISeO-2 crystallize in the chiral space grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
(92 reference statements)
0
23
0
Order By: Relevance
“…IR spectra revealed that REI 5 O 14 (RE=Y and Gd) are transparent from 2.5–11.3 μm (4000–885 cm −1 ), (Figure S8), and in Table S5 the absorption peaks were assigned in detail . The maximum IR transparent ranges are 13.6, 12.5, and 12.1 μm for RbIO 3 , NaI 3 O 8 , and CsI 4 O 11 , respectively .…”
Section: Methodsmentioning
confidence: 99%
“…IR spectra revealed that REI 5 O 14 (RE=Y and Gd) are transparent from 2.5–11.3 μm (4000–885 cm −1 ), (Figure S8), and in Table S5 the absorption peaks were assigned in detail . The maximum IR transparent ranges are 13.6, 12.5, and 12.1 μm for RbIO 3 , NaI 3 O 8 , and CsI 4 O 11 , respectively .…”
Section: Methodsmentioning
confidence: 99%
“…The reduction in ionic radii across the 4f series allows for phase changes of the afforded metal–ligand complexes. , A large family of lanthanide borates is particularly interesting because it shows a rare case of structural transitions between six distinct phases under the same synthetic conditions across the 4f series . Other systems, such as lanthanide iodate selenite, exhibit similar structural evolution with dimensional and coordination number reductions induced by the lanthanide contraction . In this work, two types of structural evolutions, from LnCuSO-1 to LnCuSO-2 and from LnCuSO-3 to LnCuSO-4 , can be observed.…”
Section: Resultsmentioning
confidence: 86%
“…In the case of NLO materials, stereo active lone pair possessing cations Se 4+ and I 5+ are commonly utilized as their possession of periodic polarizable free lone pair electrons within NSC lattices allow materials with superior second harmonic generation (SHG) properties to be obtained. A growing theme among recent NLO and SHG Se and I related material development studies has been the extension of these to uranium and actinide compounds, as it has been shown that their related properties can often exceed those of non-actinide variants [5][6][7][8]. The properties of these materials can be further improved through the increased polymerization of IO 3 − and SeO 3 2− units into polyiodate and polyselenite units [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A key component driving these promising applications is the combination of traditional functional chemical components such as stereo-active lone pair possessing IO 3 − and SeO 3 2− units with that of the uranium's unique chemical character as a 5f element which, together, drives the properties of obtained structures to often rival or excede those of non-uranium/actinide analogues [14,36]. This has been exemplified by UPI-1 and other monoiodate and monoselenite/monoselenate possessing uranyl compounds [5,6,14]. Compared to uranyl iodates, there is relatively less known about selenites and selenates in respect of synthesis conditions and control, despite the interest these receive in context of NLO and SHG materials development.…”
Section: Introductionmentioning
confidence: 99%